The Effect of Talent Management, Internal Communication and Work Life Balance on Employee Performance Through Employee Satisfaction at PT. Aru Raharja - Hasanudin, Hasanudin; Pratama, Anggara Yudha (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2023)
Employee satisfaction and its effects on employee performance at PT. Aru Raharja are influenced by talent, internal communication, and work-life balance. With the aid of the AMOS Version 24 application, data was collected from 190 respondents via questionnaires and analysed using structural equation modelling (SEM). According to the study's findings, internal communication does not significantly affect employee satisfaction (H2 is rejected), while talent management has a favourable and large impact on it. Employee Satisfaction is positively and significantly impacted by Work-Life Balance (H3 obtained). But neither Work Life Balance (H6) nor Talent Management and Internal Communication (H4 and H5 were eliminated) had a substantial impact on Employee Performance. Employee Satisfaction was also discovered to have a positive and significant impact on employee performance (H7 received). The study also found that Employee Satisfaction fully mediators the association between talent management and employee performance (H8 received), making the direct impact of talent management on employee performance negligible. Employee satisfaction, however, does not mediate between internal communication and employee performance (H9 rejected). However, Work Life Balance also fully mediates the association between Work Life Balance and Employee Performance (H10 accepted), negating the direct impact of Work Life Balance on Employee Performance.